The age of mass migration: economic and institutional determinants - Graziella Bertocchi; Chiara Strozzi (Institute for the Study of Labor (IZA), 2006)
We study the determinants of 19th century mass migration with special attention to the role of institutional factors beside standard economic fundamentals. We find that economic forces associated with income and demographic differentials had a major role in the determination of this historical event, but that the quality of institutions also mattered. We evaluate separately the impact of political institutions linked to democracy and suffrage and of those institutions more specifically targeted at attracting migrants, i.e., citizenship acquisition, land distribution, and public education policies. We find that both sets of institutions contributed to this event, even after controlling for their potential endogeneity through a set of instruments exploiting colonial history and the quality of institutions inherited from the past.
urn:nbn:de:101:1-20080509159
Keywords: 330